2018
DOI: 10.1186/s12865-018-0262-z
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologically upregulated carcinoembryonic antigen-expression enhances the cytolytic activity of genetically-modified chimeric antigen receptor NK-92MI against colorectal cancer cells

Abstract: BackgroundThe natural killer cell line, NK-92MI, is cytotoxic against various types of cancer. The aim of this study was to develop chimeric antigen receptor-modified (CAR) NK-92MI cells targeting carcinoembryonic antigen-expressing (CEA) tumours and increase killing efficacy by pharmacologically modifying CEA-expression.ResultWe generated anti-CEA-CAR NK-92MI cells by retroviral vector transduction. This genetically-modified cell line recognised and lysed high CEA-expressing tumour cell lines (LS174T) at 47.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Accordingly, combination therapy with regorafenib and CAR-NK-92 cells showed superiority over monotherapy with CAR-NK-92 cells or regorafenib in terms of inhibition of CRC growth in xenografts ( 81 ). Other in vitro studies proposed that anti- carcinoembryonic antigen (CEA)-CAR NK-92MI cells selectively recognized and eliminated high CEA-expressing CRC tumor cell lines (LS174T); without any cytolytic effects on low CEA-expressing tumor cells (HCT116) ( 86 ). Interestingly, anti-CEA-CAR NK-92MI combination therapy with either histone deacetylase-inhibitor sodium butyrate (NaB) or the methylation-inhibitor 5-azacytidine (5-AZA) caused selective killing of HCT116, which imply the clinical importance of epidrugs for prompting CAR-NK cell therapeutic efficacy in human CRC ( 86 ).…”
Section: Car Nk Cells In Solid Tumorsmentioning
confidence: 99%
“…Accordingly, combination therapy with regorafenib and CAR-NK-92 cells showed superiority over monotherapy with CAR-NK-92 cells or regorafenib in terms of inhibition of CRC growth in xenografts ( 81 ). Other in vitro studies proposed that anti- carcinoembryonic antigen (CEA)-CAR NK-92MI cells selectively recognized and eliminated high CEA-expressing CRC tumor cell lines (LS174T); without any cytolytic effects on low CEA-expressing tumor cells (HCT116) ( 86 ). Interestingly, anti-CEA-CAR NK-92MI combination therapy with either histone deacetylase-inhibitor sodium butyrate (NaB) or the methylation-inhibitor 5-azacytidine (5-AZA) caused selective killing of HCT116, which imply the clinical importance of epidrugs for prompting CAR-NK cell therapeutic efficacy in human CRC ( 86 ).…”
Section: Car Nk Cells In Solid Tumorsmentioning
confidence: 99%
“…Secondly, the dose of CAR-NK cells may be difficult to apply in vivo . Previous studies have reported the optimal anti-tumour activity for CAR-NK cells in vivo , which is 1×10 7 cells/mouse (40,41). However, the titer of the lentivirus in the present study was MOI=100.…”
Section: Discussionmentioning
confidence: 99%
“…This newly derived NK cell line can be efficiently transfected and displays similar characteristics to the parental NK-92 cells [155]. Most importantly, these cells kill cognate tumor cells and their cytotoxic capacity is associated with tumor antigen expression on target cells [156]. Induced expression of tumor antigen by epigenetic modifiers, such as sodium butyrate or DNA methylation inhibitor, as in the case of carcinoembryonic antigen in human colorectal cancer cells, promotes CAR NK-92MI-mediated cytotoxicity [156].…”
Section: Cancer Immunotherapymentioning
confidence: 99%